THE IMPLEMENTATION OF E-MODULE IN SEMANTIC CLASS AT ENGLISH STUDY PROGRAM: STUDENTS’ PERCEPTION - Sumandiyah Sumandiyah; Indah Tri Purwanti; Eliwarti Eliwarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
E-module as a learning tool is a new experience for English students. Based on the interviewing results of monitoring and information to students, it is found that the e-module has not been yet implemented or created other than in class 1 Semantic. Therefore, it is important to know how they perceive the implementation of an electronic module in the Semantic class in the English Study Program. The research in this paper aims to investigate English students’ perception of implementing the E-module in Semantic classes at the English Study Program. The research design is mixed methods (quantitative and qualitative). The data were gathered through a questionnaire and interview. Cluster random sampling was used to select the research sample, which involved 40 students. Ten students were interviewed for the qualitative data. The findings indicate that the students had a high perception of the implementation of e-module in the Semantic class. They also expect that e-module can be further developed and applied for other courses because most of them perceive e-module as a fun, complete, and total innovation in learning media that can facilitate their learning anytime and anywhere.